EFFECT NICKEL AND QUENCH-TEMPER PROCESS ON MECHANICAL AND CORROSION PROPERTIES OF ASTM A588 WAETHERING STEEL - Rohmah, Miftakhur -; Ramadhan, Gilang; Irawan, Dedi; Utama, Dedi Pria; Romijarso, Toni Bambang (Metalurgi, 2022)
The mechanical improvement and "self-protection" properties are mainly needed to develop weather-resistant steel materials. In this study, A588 steel was given thermomechanical treatment (hot-rolling) followed by a quench-tempering process. The A588 is modified by adding 1, 2, and 3 wt% nickel to the primary alloy. Steel is made using a hot rolling process at 750 ℃ for 1 hour with 70% thickness reduction. The sample is heat-treated at 850 ℃ for 1 hour and quenched in water, oil, and open air. The tempering process is conducted at 400 ℃ for 30 minutes. Metallography test is confirmed final microstructural and compared with CCT simulation result. The fast cooling (water and oil quenchant) produces tempered martensite, ferrite, and pearlite, while the air-cooled forms a ferrite-pearlite. The cooling rate significantly affects strength and hardness and the nickel addition on hardness, and both factors have no significant on ductility. The sample owns the highest tensile strength value (~1226 MPa) with 1 %Ni, and the highest ductility value (around 17.1–27.43%) is obtained by air cooling. With 3% Ni, the corrosion rate decreases to 0072 mpy with -432.5 mV for corrosion potential and 0.12µA/cm-2 for current density.